The Influence of Audio-Visual Media and Learning Motivation on The Learning Outcomes of Poetry Appreciation - Andi Panjianum; Yenny Puspita; Puspa Indah Utami (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Education is the most essential thing in life; education is a place to train someone to be skilled in language. Education can be obtained through learning both in formal and informal places. Based on the formulation of the problem, this study aimed to determine and describe the significant influence of audio-visual media on learning outcomes of class VIII poetry appreciation at SMPN 4 Abab, Pali Regency. The research method used in this study was an experiment in which the sampling was carried out using a multi-stage random sampling technique, namely determining the odd semester at SMPN 4 Abab, Pali Regency. Data were collected through observation, tests/assignments, questionnaires, and documentation. The analysis of research data processing shows that the use of medial audio-visual has a positive and significant effect on medial audio-visual learning on motivation in terms of student learning outcomes. With all the traffic, even though the working hypothesis is proven and accepted. There is a difference in students' internal poetry appreciation abilities taught with medial audio-visual in students taught with conventional learning strategies.